2014
DOI: 10.1017/s1368980014001505
|View full text |Cite
|
Sign up to set email alerts
|

Correlates of self-reported dietary cruciferous vegetable intake and urinary isothiocyanate from two cohorts in China

Abstract: Objective To assess correlations between cruciferous vegetable intake and urinary ITC level, in addition to glutathione S-transferase (GST) genotypes and other individual factors. Design This study included cohort participants whose urinary ITC levels had been previously ascertained. Urinary ITC was assessed using high-performance liquid chromatography. Usual dietary intake of cruciferous vegetables was assessed using a validated food frequency questionnaire and total dietary ITC was calculated. Recent cruci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“…The use of urinary markers to measure dietary exposure to cruciferous vegetables is a potentially valuable advance. Although statistically significant correlations between urinary ITC levels and self‐reported intake of cruciferous vegetables can be detected in human populations, the clearance of glucosinolate breakdown products from plasma is relatively rapid . Spot urine samples are therefore an indicator of recent intake rather than long‐term exposure.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of urinary markers to measure dietary exposure to cruciferous vegetables is a potentially valuable advance. Although statistically significant correlations between urinary ITC levels and self‐reported intake of cruciferous vegetables can be detected in human populations, the clearance of glucosinolate breakdown products from plasma is relatively rapid . Spot urine samples are therefore an indicator of recent intake rather than long‐term exposure.…”
Section: Discussionmentioning
confidence: 99%
“…This detoxification pathway forms part of a complex metabolic network which, as is discussed at length elsewhere in the present volume, is thought to regulate a variety of anticarcinogenic mechanisms, including the induction of ,phase II enzymes that metabolize and help to detoxify environmental carcinogens such as the constituents of tobacco smoke . Another consequence of the rapid metabolism of glucosinolate breakdown products is the appearance in human urine of their metabolites, which can be detected and quantified and used as an objective biomarker of cruciferous vegetable consumption …”
Section: Cruciferous Vegetable Consumption Gst Polymorphisms and Gamentioning
confidence: 99%
“…Estimating CV intake with quantitative biomarkers has received increasing attention (36,37). Urinary isothiocyanate, another decomposed product of glucosinolates, had been applied in previous studies (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…This finding is understandable given that urinary SFN ITC levels reflect recent intake of SFN, not usual cruciferous vegetable intake, as SFN ITC are eliminated from urine within 48 h after cruciferous vegetable intake (23) . One large study of two cohorts in China, including 3589 women and 1015 men, showed self-reported usual dietary cruciferous vegetable intake was weakly correlated with urinary ITC level (r = 0·1149, P < 0·0001), while recent dietary cruciferous vegetable intake was more strongly correlated with urinary ITC level (r = 0·2591, P < 0·0001) (24) . In our analysis of the relationship between total cruciferous vegetable intake and PBMC HDAC activity, we did not observe a significant correlation.…”
Section: Discussionmentioning
confidence: 99%